2001
DOI: 10.1039/b103645a
|View full text |Cite
|
Sign up to set email alerts
|

Phase-transfer catalyst separation and re-use by solvent resistant nanofiltration membranes

Abstract: This communication describes the use of nanofiltration (NF) membranes for efficient separation and recycling of phasetransfer catalysts, using the conversion of bromoheptane into iodoheptane with tetraoctylammonium bromide as the PT catalyst, as an example; a solvent flux of > 10 L m 22 h 21 was achieved with > 99% catalyst recycle and no loss in PT catalyst activity over a cycle of three consecutive reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…From the above two experiments, it is clear that Cu(II), Cl -and O2 are the active components of the etchant. It appears that the quaternary salts adsorbed on {111} facets of Au microcrystals (obtained from AuToABr) get removed during toluene washing due to the high solubility of the ToABr in toluene (380 g/L) [40], while Br -may remain intact on{100} facets due to poor solubility in toluene. Hence the {111} facets are easily accessible for the etchant which is devoid of the capping agent.…”
Section: Etching Of {111} Facetsmentioning
confidence: 99%
“…From the above two experiments, it is clear that Cu(II), Cl -and O2 are the active components of the etchant. It appears that the quaternary salts adsorbed on {111} facets of Au microcrystals (obtained from AuToABr) get removed during toluene washing due to the high solubility of the ToABr in toluene (380 g/L) [40], while Br -may remain intact on{100} facets due to poor solubility in toluene. Hence the {111} facets are easily accessible for the etchant which is devoid of the capping agent.…”
Section: Etching Of {111} Facetsmentioning
confidence: 99%
“…Most importantly, the concentrated solution can catalyze the reaction in fresh organic reactant solution directly without any further purification or treatment. 173,174 Compared with the recovery of phase transfer catalysts, SRNF should be more suitable to recover homogeneous catalysts, especially transition metal catalysts. [175][176][177][178][179][180][181][182][183] Schoeps et al 178 developed a type of PDMS SRNF membrane on a PAN porous support and thermally cross-linked the membranes.…”
Section: Recovery Of Catalystsmentioning
confidence: 99%
“…Sheth et al 165 claimed that precompacting commercial MPF-50 or MPF-60 with used solvents at operational pressures and temperatures is necessary to remove erythromycin because precompaction increased the rejection of erythromycin by SRNF membranes, which reduced the loss of erythromycin and increased the purification efficiency. Shi et al 166 fabricated a type of PI membrane to concentrate spiramycin 220 (n-alkanes in toluene) [168][169][170][171][173][174][175]180,182,184,[190][191][192]195,197 Starmem TM 228 280 (n-alkanes in toluene) 169,179,184,196 Starmem TM 240 400 (n-alkanes in toluene) [171][172][173][174][175]180,182,184,185,189,196,197 Puramem TM extracts and recover the used solvent (butyl acetate). They indicated that the permeability of the spiramycin solution was significantly affected by the operating conditions, although the rejection of spiramycin (higher than 99%) was not influenced.…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PTC remains in the retentate phase and is recycled to the next reaction. More detailed accounts of this technique can be found elsewhere 17,18…”
Section: Homogeneous Catalyst Recyclementioning
confidence: 99%